Enhanced piezoelectric properties in LixBi1-xNbxFe1-xO3 films contributed by low-symmetry phase and self-polarization. Issue 3 (15th February 2019) - Hou, Yafei; Han, Renlu; Liu, Yang; Luo, Laihui; Li, Weiping; Fei, Weidong
Abstract: Li x Bi1- x Nb x Fe1- x O3 films with various Li + and Nb 5+ substitutions were fabricated onto LaNiO3 -buffered Pt(111)/Ti/SiO2 /Si substrates through sol-gel methods. Owing to the substitution by smaller Li + and Nb 5+ for larger Bi 3+ and Fe 3+ respectively, the phase structure of Li x Bi1- x Nb x Fe1- x O3 films experiences a transition from rhombohedral phase (R phase, high symmetry) to tetragonal-like phase (T-like, low-symmetry) upon the chemical pressure with Li + and Nb 5+ substitution increases. Additionally, the dielectricity, ferroelectricity and leakage behaviors of substituted Li x Bi1- x Nb x Fe1- x O3 films are also significantly improved. More importantly, the substituted Li x Bi1- x Nb x Fe1- x O3 films show significantly enhanced piezoelectric responses, especially for the Li0.05 Bi0.95 Nb0.05 Fe0.95 O3 film, whose d 33 with the value of 107.5 pm/V might be compared with some lead-based piezoelectric films. The enhanced piezoelectric response of the Li0.05 Bi0.95 Nb0.05 Fe0.95 O3 film is contributed by synergistic effects of low-symmetry phase, improved ferroelectricity and downward self-polarization, where the electric field-triggered R-T phase transition and polarization vectors rotation can be easily took place upon small stimuli. Additionally, the reduction of leakage currents for substituted Li x Bi1- x Nb x Fe1- x O3 films also help to improve their dielectric, ferroelectric and piezoelectric properties.